The impact of irrigation farming in transforming livelihoods in rural communities: the case of Nyanga district, ward 12 - Nyakatawa, Rachel (Midlands State University, 2018)
The study examined the impact of irrigation farming in transforming rural livelihoods. The research’s case study was Nyamaropa Irrigation Scheme located in Ward 12 of Nyanga District, south east of the district. Qualitative methodology was used during the study, and two types of data gathering instruments that are questionnaires and interviews, were used to obtain a sample of one hundred irrigators, forty-nine non-irrigators and one AGRITEX officer. A total of one hundred questionnaires and fifty interviews were carried out. The results were based on information captured in the questionnaires and face to face interactions. Also purposive type of sampling was used. The study found that irrigation farming has positive and negative impacts in transforming rural livelihoods. Results from the study show that irrigation farming in the study area has transformed livelihoods in rural communities. The farming has resulted in economic development as witnessed by improved household incomes, creation of employment for both irrigation and non-irrigation farmers, introduction of new crops, new administrative and economic structures and non-farm activities which increase employment. Irrigation farming has also resulted in social development of the community with sustainability implications such as food security, poverty eradication, reduction of migration, improved social services, gender equality, resettlement of people, scheme management, new forms of governance and distinction between irrigation and non-irrigation farmers. In addition to that, irrigation farming has resulted in infrastructural development as witnessed by the tarred road, improvement of houses and their electrification. Irrigation farming also resulted in infrastructural development also witnessed by the conservation of natural resources by irrigation farmers. The farming also resulted in cultural as noticed by many churches which were introduced in the community. However, some challenges were noticed such as water shortage, unfair distribution of water, lack of markets and marketing facilities, small plots resulting in small scale of production, vi illiteracy of farmers, lack of agricultural inputs, pests and insects in the irrigation farm, health problems, conflicts and failure to access credit by farmers. Despite these challenges, irrigation farming has remained successful in transforming the livelihoods of irrigation farmers.